Analisis Aspek Hukum dalam Studi Kelayakan Bisnis: Studi pada BMT UGT Nusantara - Dewaji, Jannara; Fauzan, Iqbal Zul; Anliwiarta, Zhuvido; Rifqi, Muhammad; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the legal aspects in the business feasibility study of BMT UGT Nusantara, a cooperative-based Islamic financial institution. The study highlights relevant regulations, such as the Sharia Cooperative and Banking Law, as well as compliance with applicable regulations. The method used is descriptive analysis with a qualitative approach based on primary and secondary data. The results of the study show that BMT UGT Nusantara is legally feasible, by meeting all legality requirements including business licenses, locations, and disturbances. The study also emphasizes the importance of a strong legal foundation to protect all parties involved and support the operational sustainability of the institution. This study provides strategic recommendations for the development of sharia-based microfinance businesses that are law-abiding.